PERUBAHAN KARAKTER ANAK SEKOLAH DASAR AKIBAT PENGGUNAAN TEKNOLOGI - Anas Tasya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has had a significant impact on various aspects of life, including the behavior and character of elementary school children. This study aims to examine the changes in character that occur in elementary school children due to the use of technology, especially digital devices such as smartphones, tablets, and computers. The method used is a literature study. The results of the study show that the use of technology has both positive and negative impacts. On the one hand, technology can improve children's cognitive abilities, creativity, and access to information. However, on the other hand, excessive use of technology has the potential to reduce empathy, reduce direct social interaction, and foster consumer behavior and dependence on gadgets. Therefore, the active role of parents and teachers is needed in guiding and supervising the use of technology so that children can grow with balanced and positive characters.